The Effect of Chicken Cage Fertilizer with Dosage of Waste Shrimp on Growth and Production of Sweet Corn (Zea mays saccharata Sturt) - Zahanis Zahanis; Siska Siska; Ermawati Ermawati (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Test Effect of Chicken Manure Enriched with Shrimp Waste Dosage in order to determine the effect of chicken manure enriched with shrimp waste dose on growth and production of sweet corn plants. This experiment used a randomized block design (RAK) consisting of Factor U, namely 20 tons/ha of chicken manure with several levels of shrimp waste dose, namely 0 ml of shrimp waste/l, 3 ml of shrimp waste/l, 6 ml of shrimp waste/l, 9 ml of shrimp waste/l, 12 ml of shrimp waste/l and 6 ml/l of chitosan. Based on the experimental results, it can be concluded that the application of chicken manure enriched with a dose of shrimp waste was able to increase the growth and production of sweet corn plants with the best dose of chicken manure + 12 ml/l of shrimp waste.